Dakhil dalam Tafsir: Analisis Pengaruh Eksternal Terhadap Penafsiran Ayat-Ayat Bernuansa Politik dalam Al-Qur’an: Dakhil in Tafsir: An Analysis of External Influences on the Interpretation of Politically Nuanced Verses in the Qur'an - Hermawan, Wendy; Wahdiyat Hamdi; Naufal Akram; Muhammad Ichza Naufal (CV Kalimasada Group, 2025)
This study aims to identify and analyze several deviant interpretations, particularly those related to political verses in the Qur'an. The existence of dakhil in the interpretation of the Qur'an is unavoidable. Various ideological interests have led to distortions in the interpretation of Qur'anic verses, which continue to persist in certain exegetical works. Therefore, in-depth research is necessary to examine this phenomenon in order to safeguard the understanding of the Muslim community from misleading interpretations. Using a qualitative research approach based on a literature review and comparative analysis, this study seeks to provide insight into how certain groups have failed to interpret the Divine Word with integrity. The findings indicate that several sects within Islam, such as Shia, Murji’ah, Ahmadiyya, and Khawarij, interpret the Qur'an based on their ideological interests, often without adhering to the interpretive principles agreed upon by the majority of scholars. These deviations not only stray from the authentic methods of exegesis but also contribute to conflicts and divisions within the Muslim community. Therefore, a correct and scholarly understanding of the Qur'an is essential to prevent people from being misled by interpretations that deviate from the truth.